2024
DOI: 10.1007/s40626-023-00304-1
|View full text |Cite
|
Sign up to set email alerts
|

Motor cognition in plants: from thought to real experiments

Bianca Bonato,
Umberto Castiello,
Silvia Guerra
et al.

Abstract: Motor cognition involves the process of planning and executing goal–directed movements and recognizing, anticipating, and interpreting others’ actions. Motor cognitive functions are generally associated with the presence of a brain and are ascribed only to humans and other animal species. A growing body of evidence suggests that aneural organisms, like climbing plants, exhibit behaviors driven by the intention to achieve goals, challenging our understanding of cognition. Here, we propose an inclusive perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…An increasing number of studies have suggested that plant and animal behaviours show strong similarities (e.g., decision-making, learning) and that a neural architecture is not ubiquitously necessary to support certain abilities [44][45][46][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. However, how can we trace a territory in which handedness for animals and plants can coexist and, more importantly, be revealed?…”
Section: Toward a Comparative Study Of Handedness In Animals And Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have suggested that plant and animal behaviours show strong similarities (e.g., decision-making, learning) and that a neural architecture is not ubiquitously necessary to support certain abilities [44][45][46][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. However, how can we trace a territory in which handedness for animals and plants can coexist and, more importantly, be revealed?…”
Section: Toward a Comparative Study Of Handedness In Animals And Plantsmentioning
confidence: 99%
“…Recently, the kinematical approach has been extended to the study of goal-directed movement in plants. In specific, the approaching and clasping movements performed by different organs of a pea plant towards a potential support have been characterized [44][45][46][48][49][50][51][52][53][54][55]63,73]. These findings have demonstrated that pea plants are able to perceive an element in the environment and to modulate the kinematics of their movement in terms of velocity, acceleration, aperture of their tendrils, and smoothness on the basis of the feature of the to-be-grasped support [45,[51][52][53][54][55], the task (e.g., decision-making) [46,63], and the context (e.g., competition or cooperation) [44,48].…”
Section: Toward a Comparative Study Of Handedness In Animals And Plantsmentioning
confidence: 99%